Study of genetic divergence in rice (Oryza sativa L.) genotypes with high grain zinc using Mahalanobis’ D2 analysis - Singh, S. K.; Pandey, Vishal; Korada, Mounika; Singh, D. K.; Khaire, A. R.; Habde, Sonali; Majhi, Prasanta Kumar (EJPB, ISPB, CPBG - Tamil Nadu Agricultural University, 2020)
The present investigation was conducted with twenty-two genotypes of rice during Kharif, 2018 in RBD with three replications in five different locations. The 22 rice genotypes were characterized based on 16 quantitative traits viz., days to first flowering, days to 50 per cent flowering, days to maturity, the total number of effective tillers per plant, plant height (cm), panicle length (cm), the number of spikelets per panicle, the number of grains per panicle, spikelet fertility percentage, grain weight per panicle (g), grain yield per plant (g) , 1000-grain weight (g), grain yield per plot (kg), grain yield per hectare (kg), grain L/B Ratio, grain zinc content (ppm or mg /kg) using Mahalanobis D2 statistic. D2 analysis distributed the 22 genotypes into six clusters, of which cluster I was the largest with 15 genotypes. Cluster II had maximum intra-cluster values of 5.16 and the maximum inter-cluster distance was observed between the clusters III and V (40.51) followed by cluster IV and V (28.39) indicating the importance of the genotypes present in these clusters for exploiting heterosis for the desirable traits of these clusters.